2013
DOI: 10.1039/c3fo60041f
|View full text |Cite
|
Sign up to set email alerts
|

Anti-inflammatory effects of phenolic compounds isolated from the flowers of Nymphaea mexicana Zucc.

Abstract: Nymphaea mexicana Zucc. is an aquatic plant species which belongs to the family Nymphaea and is commonly known as the yellow water lily. The aim of this work was to study the in vitro antiinflammatory effects of phenolic compounds isolated from the flowers of Nymphaea mexicana Zucc. Seven phenolic compounds including vanillic acid, 4-methoxy-3,5-dihydroxybenzoic acid, (2R,3R)-3,7-dihydroxyflavanone, naringenin (4), kaempferol 3-O-(3-O-acetyl-a-L-rhamnopyranoside), kaempferol 3-O-(2-O-acetyl-a-L-rhamnopyranosid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(29 citation statements)
references
References 41 publications
0
26
0
3
Order By: Relevance
“…Hsu et al showed that naringenin extracted from Nymphaea mexicana Zucc. has an important inhibitory effect on MCP-1 and TNF-α production in LPS-activated RAW264.7 macrophages by decreasing the expression of iNOS and ERK phosphorylation [229]. The anti-inflammatory effects of naringenin in vivo were evaluated by Raza et al, demonstrating that naringenin treatment downregulates the NF-κB expression levels in the brains of Wistar rats after the cerebral I/R injury [230].…”
Section: Flavanolsmentioning
confidence: 99%
“…Hsu et al showed that naringenin extracted from Nymphaea mexicana Zucc. has an important inhibitory effect on MCP-1 and TNF-α production in LPS-activated RAW264.7 macrophages by decreasing the expression of iNOS and ERK phosphorylation [229]. The anti-inflammatory effects of naringenin in vivo were evaluated by Raza et al, demonstrating that naringenin treatment downregulates the NF-κB expression levels in the brains of Wistar rats after the cerebral I/R injury [230].…”
Section: Flavanolsmentioning
confidence: 99%
“…Total phenolics and the antioxidant capacities of ten flowers were measured in China; the results indicated that flowers were good sources of phenolics and antioxidants (Xiong et al, 2014). Other researchers have also indicated that flowers are rich in phenolic compounds and have great antioxidant activity, as well as the capacity to inhibit some chronic diseases (Besbes et al, 2013;Hsu, Fang, & Yen, 2013;Lin, Chung, & Hsu, 2012). In previous studies, large amounts of organic solvents were used to extract antioxidants from flowers (Xiong et al, 2014); however organic solvents are unsafe to researchers and unfriendly to the environment.…”
Section: Introductionmentioning
confidence: 98%
“…4 d-galactose can also affect oxidative biomarkers, such as superoxide dismutase (SOD) and malondialdehyde (MDA) and change the total antioxidant status in the blood, brain, and liver. 5 Therefore, d-galactose-induced aging is often used as a model of aging. 6,7 Phenylethanoid glycosides (PeGs) are present in more than 150 species of plants belonging to 20 families and 77 genera.…”
Section: Introductionmentioning
confidence: 99%